Credentialing results from IMRT irradiations of an anthropomorphic head and neck phantom. Issue 2 (8th January 2013) - Molineu, Andrea; Hernandez, Nadia; Nguyen, Trang; Ibbott, Geoffrey; Followill, David
Abstract : Purpose: : This study was performed to report and analyze the results of the Radiological Physics Center's head and neck intensity‐modulated radiation therapy (IMRT) phantom irradiations done by institutions seeking to be credentialed for participation in clinical trials using intensity modulated radiation therapy. Methods: : The Radiological Physics Center's anthropomorphic head and neck phantom was sent to institutions seeking to participate in multi‐institutional clinical trials. The phantom contained two planning target volume (PTV) structures and an organ at risk (OAR). Thermoluminescent dosimeters (TLD) and film dosimeters were imbedded in the PTV. Institutions were asked to image, plan, and treat the phantom as they would treat a patient. The treatment plan should cover at least 95% of the primary PTV with 6.6 Gy and at least 95% of the secondary PTV with 5.4 Gy. The plan should limit the dose to the OAR to less than 4.5 Gy. The passing criteria were ±7% for the TLD in the PTVs and a distance to agreement of 4 mm in the high dose gradient area between the PTV and the OAR. Pass rates for different delivery types, treatment planning systems (TPS), linear accelerators, and linear accelerator‐planning system combinations were compared. Results: : The phantom was irradiated 1139 times by 763 institutions from 2001 through 2011. 929 (81.6%) of the irradiations passed the criteria. 156 (13.7%) irradiations failed only the TLD criteria, 21 (1.8%) failed only the film criteria, and 33 (2.9%) failed both sets of criteria. Only 69% of the irradiations passed a narrowed TLD criterion of ±5%. Varian‐Elipse and TomoTherapy‐HiArt combinations had the highest pass rates, ranging from 90% to 93%. Varian‐Pinnacle 3, Varian‐XiO, Siemens‐Pinnacle 3, and Elekta‐Pinnacle 3 combinations had pass rates that ranged from 66% to 81%. Conclusions: : The head and neck phantom is a useful credentialing tool for multi‐institutional IMRT clinical trials. The most commonly represented linear accelerator‐planning system combinations can all pass the phantom, though some combinations had higher passing percentages than others. Tightening the criteria would significantly reduce the number of institutions passing the credentialing criteria. Causes for failures include incorrect data entered into the TPS, inexact beam modeling, and software and hardware failures.